Conversion of sustainable oils to jet fuels using low pressure green hydrogen

By using weakly crystalline metal sulfide catalysts under low pressure conditions, palm oil and rubber are converted into sustainable aviation fuel, solving the problems of high-pressure hydrogen assisted and catalyst activity in the prior art, and achieving efficient and environmentally friendly fuel production.

CN119894602APending Publication Date: 2025-04-25PETROLIAM NASIONAL BHD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056751.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art requires high-pressure hydrogen assistance when converting oil from renewable raw materials into jet fuel, and the catalyst activity is significantly reduced under low hydrogen conditions, affecting process efficiency and environmental performance.

Method used

The catalyst is prepared by calcining sulfur-containing metal organic compounds or thio metallic acids under an inert atmosphere using a synergistic process based on palm oil and rubber, using a weakly crystalline metal sulfide catalyst, achieving the ability to convert oil into fuel under low pressure conditions.

Benefits of technology

It realizes the production of fully sustainable aviation fuel without adding external hydrogen supply, which improves process efficiency and environmental performance and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894602A_ABST
    Figure CN119894602A_ABST
Patent Text Reader

Abstract

Disclosed herein is a weakly crystalline metal sulfide catalyst, wherein the catalyst comprises Mo and / or W in a total amount of 25 to 35 wt%, Ni and / or Co in a total amount of 0 to 25 wt%, S in an amount of 20 to 28 wt%, N or P in an amount of 0 to 5 wt%, and C in an amount of 10 to 54 wt%. Also disclosed herein are methods of forming the catalysts and producing deoxygenated organic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to converting sustainable oils into fuels by using catalysts and low-pressure green hydrogen. Background Art

[0002] The listing or discussion of a previously published document in this specification should not be taken as an admission that the document is part of the prior art or is common general knowledge.

[0003] The global aviation industry, led by the International Civil Aviation Organization (ICAO), has pledged to reduce carbon emissions from aviation and has adopted the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA). The scheme complements the reduction of net carbon emissions to a baseline level (2020 CO 2 PETRONAS is committed to implementing several measures required to meet CORSIA standards, including the use of sustainable aviation fuel (SAF). To meet CORSIA requirements, PETRONAS intends to develop a chemical process to produce sustainable aviation fuel (SAF) based on abundantly available Malaysian raw materials such as palm oil, biomass and natural rubber. The formulated fuel containing bio-components must meet commercial jet fuel grade specifications (i.e. Jet A and Jet A-1).

[0004] Thermal cracking of natural rubber produces a mixture of cyclic hydrocarbons and unsaturated hydrocarbons (limonene and isoprene). Palm oil can be catalytically hydrogenated into fuel, an existing technology called HEFA-SPK, which hydrogenates esters and fatty acids into synthetic paraffin kerosene. However, HEFA-SPK consumes a lot of hydrogen (H 2 ), the SAF produced by this process can only be mixed into existing petroleum-based aviation fuels, with a maximum of 50% by volume. In addition, most of the H 2 It is brown H from fossil fuels 2 , which may affect the life cycle analysis emissions of this pathway.

[0005] The commercial HEFA-SPK technology uses high-pressure molecular hydrogen (typically 40-110 bar) to remove oxygenates from sustainable oils in a reaction process called hydrodeoxygenation (HDO). Since limonene dehydrogenation produces less than 1 bar of green hydrogen, this low hydrogen partial pressure needs to be compensated with a highly active catalyst to drive the HDO reaction to completion.

[0006] Typical existing methods for synthesizing commercial HDO catalysts include the isovolumetric impregnation (IWI) method, in which active metals such as molybdenum, Mo, and tungsten, W, are deposited on supports such as alumina or zeolites. This method inherently limits the amount of active metals because no chemical reaction occurs between the active metal precursors and the support during the IWI process. While such catalysts are sufficient for high-pressure hydrogen-assisted HDO processes, HDO activity decreases significantly when limonene is used as the sole hydrogen source.

[0007] Therefore, there is a need to develop new materials and methods for converting oil from renewable raw materials into jet fuel. Summary of the invention

[0008] Surprisingly, it has been found that the above mentioned problems can be solved by a synergistic process based on two natural resources: palm oil and rubber, which can produce a completely sustainable aviation fuel without adding an external hydrogen supply. This can be achieved by using the metal sulfide catalysts and / or methods described below.

[0009] Various aspects and embodiments of the invention are provided by the following numbered clauses.

[0010] 1. A poorly crystalline metal sulfide catalyst, wherein the catalyst comprises:

[0011] Mo and / or W in a total amount of 25 to 35 wt.%;

[0012] A total amount of 0 wt% to 25 wt% Ni and / or Co;

[0013] S in an amount of 20 to 28 wt %;

[0014] N or P in an amount of 0 to 5 wt%; and

[0015] 10 to 54 wt. % C, wherein:

[0016] When Mo and W are present, they are in the form of MoS 2 and / or MoS 3 , WS 2 and / or WS 3 Or Mo a W 1-a S y In the form of particles, wherein a is from 0.99 to 0.01, and y is 2 and / or 3; and

[0017] The crystallinity of the catalyst measured by powder X-ray crystal diffraction is less than 80%.

[0018] 2. The catalyst according to clause 1, wherein the catalyst has a BET surface area of ​​75 m 2 / g to 100m 2 / g.

[0019] 3. The catalyst according to clause 1 or clause 2, wherein the catalyst comprises:

[0020] Mo and / or W in a total amount of 25 to 35 wt.%;

[0021] A total amount of 0 wt% to 25 wt% Ni and / or Co;

[0022] S in an amount of 20 to 28 wt %;

[0023] N or P in an amount of 0 to 5 wt%; and

[0024] 32 to 54 wt% C; or

[0025] Mo and / or W in a total amount of 27 to 30 wt.%;

[0026] A total amount of 0 to 20 wt% Ni and / or Co;

[0027] S in an amount of 22 to 24 wt %;

[0028] N or P in an amount of 3 to 4 wt%; and

[0029] The content of C is 42% to 48% by weight.

[0030] 4. A catalyst according to any one of the preceding clauses, wherein the catalyst comprises:

[0031] Mo in a total amount of 25 wt% to 35 wt%;

[0032] S in an amount of 20 to 28 wt %;

[0033] N or P in an amount of 1 to 5 wt%; and

[0034] The content of C is 32% to 54% by weight.

[0035] 5. The catalyst according to clause 4, wherein the catalyst comprises:

[0036] Mo in an amount of 27 to 30 wt %, for example about 28.9 wt %;

[0037] S in an amount of 22 to 24 wt %, for example, about 23.2 wt %;

[0038] N or P in an amount of 3 to 4 wt%, for example, about 3.5 wt%; and

[0039] The content of C is 42% to 48% by weight, for example, about 44.4% by weight.

[0040] 6. The catalyst according to clause 4 or clause 5, wherein the X-ray powder diffraction pattern exhibits broad peaks having 2θ values ​​of about 33° and about 59°.

[0041] 7. The catalyst according to any one of clauses 4 to 6, wherein the BET surface area is about 83.6 m 2 / g.

[0042] 8. A catalyst according to any one of the preceding clauses, wherein:

[0043] (a) the catalyst has a crystallinity of less than 70%, such as less than 60%, such as less than 50%; and / or

[0044] (b) The catalyst is attached to a solid support, optionally wherein the solid support is silica or a ceramic (eg Y-zeolite).

[0045] 9. A method of forming a catalyst according to any one of clauses 1 to 8, the method comprising the steps of:

[0046] (a) providing a sulfur-containing metal organic compound or a thiometallate salt; and

[0047] (b) calcining the sulfur-containing metal organic compound or thiometalate under an inert gas flow at a temperature of 300° C. to 400° C. for a period of time to provide the catalyst.

[0048] 10. The method according to clause 9, wherein the temperature is increased at a rate of 3 to 4°C per minute, such as about 3.5°C per minute, until the target temperature is reached.

[0049] 11. A method according to clause 9 or clause 10, wherein:

[0050] (i) the temperature is about 350°C; and / or

[0051] (ii) prior to step (b) of clause 9, homogeneously mixing the sulfur-containing metal organic compound or thiometallate with a solid support, optionally wherein the solid support is silica or ceramic (eg Y-type zeolite).

[0052] 12. A method according to any of clauses 9 to 11, wherein the time period after reaching a temperature of 300°C to 400°C is 2 to 3 hours, such as about 2.5 hours.

[0053] 13. The method according to any one of clauses 9 to 12, wherein the inert gas is nitrogen.

[0054] 14. A method for producing a deoxygenated organic material, the method comprising:

[0055] (a) providing an oxygen-containing raw material and a catalytic material suitable for converting the oxygen-containing raw material into a deoxygenated organic material; and

[0056] (b) contacting the oxygen-containing raw material with the catalytic material in a reaction vessel at a temperature of 275°C to 400°C, such as 300°C to 380°C, at a gas pressure of less than or equal to 2,000 kPa (20 bar) for a period of time to provide the deoxygenated organic material, wherein:

[0057] The oxygen-containing raw material is selected from one or more of the group consisting of triglycerides, fatty acids and fatty acid esters;

[0058] The gas pressure is provided by hydrogen alone, or by hydrogen and an inert gas, wherein the hydrogen is provided by an external hydrogen source and / or is provided internally by hydrogen released from a hydrogen donor; and

[0059] The catalytic material suitable for converting the oxygen-containing raw material into a deoxygenated organic material is selected from one or more of the group consisting of: a catalyst according to any one of clauses 1 to 8 and a commercially available CoMo catalyst (eg, a catalyst according to any one of clauses 1 to 8).

[0060] 15. The method of clause 14, wherein the pressure is about 1,000 kPa.

[0061] 16. The method according to clause 14 or clause 15, wherein the gas pressure is provided by hydrogen and nitrogen, and the hydrogen is provided internally by hydrogen released by the hydrogen donor.

[0062] 17. The method according to any one of clauses 14 to 16, wherein the hydrogen donor is limonene.

[0063] 18. A method according to any one of clauses 14 to 17, wherein the weight ratio of the catalytic material to the oxygen-containing raw material is from 1:15 to 1:50, such as about 1:19.

[0064] 19. A method according to any one of clauses 14 to 18, wherein, when a hydrogen donor is present, the weight ratio of the oxygen-containing raw material to the hydrogen donor is from 1:5 to 1:50, such as about 1:9.

[0065] 20. A method according to any one of clauses 14 to 29, wherein the raw material is selected from one or more of the following: palm oil (e.g. refined palm oil), algal oil (e.g. crude algal oil), canola oil / rapeseed oil, soybean oil, corn oil, sunflower oil, animal fat, olive oil (e.g. virgin or used olive oil), peanut oil, castor oil and animal fat.

[0066] 21. The method according to any one of clauses 14 to 29, wherein the sulfur-containing metal organic compound or thiometallate is an ionic liquid having formula I:

[0067] [R 1 R 2 R 3 R 4 X] 2 [B x' (A x S y O z ) a' ] I

[0068] in:

[0069] A is selected from one or more of Mo and W;

[0070] When B is present, it is Co and / or Ni;

[0071] x is 1 to 3;

[0072] x' is 0 or 1;

[0073] y is 1 to 13;

[0074] z is 0 to 3;

[0075] a' is 1 or 2;

[0076] R 1 It is C 1 To C 3 alkyl;

[0077] R 2 To R 4 Each independently selected from C 5 To C 20 Alkyl; and

[0078] X is N or P. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 Shown is the MoSx catalyst after calcination under inert atmosphere.

[0080] Figure 2 Scanning electron microscope (SEM) micrographs of MoSx catalysts are shown.

[0081] Figure 3 It shows that MoS 2 Powder X-ray diffraction (PXRD) patterns of the characterized MoSx catalysts. DETAILED DESCRIPTION

[0082] Surprisingly it has been found that a new form of metal sulfide catalyst can be produced using a simple process which produces a material that is weakly crystalline but has improved performance over conventional metal sulfide catalysts. Therefore, in a first aspect of the present invention there is provided a weakly crystalline metal sulfide catalyst, wherein the catalyst comprises:

[0083] Mo and / or W in a total amount of 25 to 35 wt.%;

[0084] A total amount of 0 wt% to 25 wt% Ni and / or Co;

[0085] S in an amount of 20 to 28 wt %;

[0086] N or P in an amount of 0 to 5 wt%; and

[0087] 10 to 54 wt. % C, wherein:

[0088] When Mo and W are present, they are in the form of MoS 2 and / or MoS 3 , WS 2 and / or WS 3 Or Mo a W 1-a S y In the form of particles, wherein a is from 0.99 to 0.01, and y is 2 and / or 3; and

[0089] The crystallinity of the catalyst measured by powder X-ray crystal diffraction is less than 80%.

[0090] In the embodiments herein, the term "comprising" may be interpreted as requiring the features described, but not limiting the presence of other features. Alternatively, the term "comprising" may also refer to situations where only the listed components / features are intended to be present (e.g., the term "comprising" may be replaced by the phrase "consisting of" or "consisting essentially of"). It is expressly contemplated that both broader and narrower interpretations may apply to all aspects and embodiments of the present invention. In other words, the term "comprising" and its synonyms may be replaced by the phrase "consisting of" or the phrase "consisting essentially of" or their synonyms, and vice versa.

[0091] As used herein, the term "weakly crystalline" refers to a material that may be amorphous or have some ill-defined crystalline peaks in a powder X-ray diffraction pattern. As described above, the level of crystallinity in the catalytic material may be up to but not more than 80% of the material. In specific embodiments that may be mentioned herein, the crystallinity of the catalyst may be less than 70%, such as less than 60%, such as less than 50% of the catalytic material. More specifically, the crystallinity of the catalyst may be less than 40%, less than 30%, less than 20%, such as less than 10%. In further embodiments, the material may be almost completely amorphous or completely amorphous.

[0092] Measurement of the level of crystallinity can be achieved by comparing a catalyst measured using the same measurement parameters to a pure crystalline sample of the same material. It should be understood that crystallinity measured in this manner may not be completely quantitative, and therefore the above crystallinity values ​​may contain a certain degree of error (e.g., an error of 0 to 10%, such as an error of about 5%). However, it is possible to determine whether a material is substantially crystalline or substantially amorphous based on an X-ray diffraction pattern of a sample catalyst without reference to an X-ray diffraction pattern of a completely crystalline sample, and if such a diffraction pattern is provided, a reasonable approximation of the overall crystallinity of the sample catalyst can be determined.

[0093] The above aspect can be expressed in another way: a sulfide catalyst is provided, wherein the catalyst comprises:

[0094] Mo and / or W in a total amount of 25 to 35 wt.%;

[0095] A total amount of 0 wt% to 25 wt% Ni and / or Co;

[0096] S in an amount of 20 to 28 wt %;

[0097] N or P in an amount of 0 to 5 wt%; and

[0098] 10 to 54 wt. % C, wherein:

[0099] When Mo and W are present, they are in the form of MoS 2 , WS 2 Or Mo a W 1-a S 2 In the form of particles, wherein a is from 0.99 to 0.01; and

[0100] At least 20% of the catalyst is in amorphous form as measured by powder X-ray crystallography.

[0101] In such embodiments, the amount of amorphous material may be greater than 30%, greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or the material may be almost completely amorphous or completely amorphous.

[0102] It is understood that the above versions of this aspect are nothing more than the same catalytic material being represented by the presence of an amorphous material. Therefore, it is worth noting that the same changes can also be made to the representation of other materials listed herein.

[0103] The catalysts disclosed herein are provided in a particle form. Thus, the catalysts have a measurable surface area. In some embodiments of the present invention, the BET surface area of ​​the catalyst may be 75 m 2 / g to 100m 2 / g. For example, the BET surface area can be 83.6 m 2 / g.

[0104] In an embodiment of the present invention, the catalyst may comprise:

[0105] Mo and / or W in a total amount of 25 to 35 wt.%;

[0106] A total amount of 0 wt% to 25 wt% Ni and / or Co;

[0107] S in an amount of 20 to 28 wt %;

[0108] N or P in an amount of 0 to 5 wt%; and

[0109] The content of C is 32% to 54% by weight.

[0110] In a further embodiment of the present invention, the catalyst may comprise:

[0111] Mo and / or W in a total amount of 27 to 30 wt.%;

[0112] A total amount of 0 to 20 wt% Ni and / or Co;

[0113] S in an amount of 22 to 24 wt %;

[0114] N or P in an amount of 3 to 4 wt%; and

[0115] The content of C is 42% to 48% by weight.

[0116] In a further embodiment of the present invention, the catalyst may comprise:

[0117] Mo in a total amount of 25 wt% to 35 wt%;

[0118] S in an amount of 20 to 28 wt %;

[0119] N or P in an amount of 1 to 5 wt%; and

[0120] The content is 32% to 54% by weight of C. More specifically, the catalyst may comprise:

[0121] Mo in an amount of 27 to 30 wt %, for example about 28.9 wt %;

[0122] S in an amount of 22 to 24 wt %, for example, about 23.2 wt %;

[0123] N or P in an amount of 3 to 4 wt%, for example, about 3.5 wt%; and

[0124] The content of C is 42 wt % to 48 wt %, for example, about 44.4 wt %. In these embodiments, the X-ray powder diffraction pattern can show broad peaks with 2θ values ​​of about 33° and about 59°. In addition, in these embodiments, the BET surface area can be about 83.6 m 2 / g.

[0125] Although the catalyst can be provided as a separate independent component, it can also be provided on a solid support. Suitable solid supports include, but are not limited to, silica and ceramics (e.g., Y-type zeolite). It will be appreciated that when a solid support is included, the BET surface area of ​​the resulting catalyst may be affected by the presence of these particles. Thus, the range of BET surface area can be wider, for example, from 30 m 2 / g to 450m 2 / g.

[0126] The catalyst disclosed herein can be prepared using a simple and economical method. Therefore, in another aspect of the present invention, a method for forming the catalyst as described above is provided, the method comprising the following steps:

[0127] (a) providing a sulfur-containing metal organic compound or a thiometallate; and

[0128] (b) calcining the sulfur-containing metal organic compound or thiometalate under an inert gas flow at a temperature of 300° C. to 400° C. for a period of time to provide the catalyst.

[0129] When used herein, the term "sulfur-containing metal organic compound or thiometalate" refers to any material including sulfur and the metals mentioned above (e.g., at least one of Mo and W, and optionally at least one of Ni and Co). Examples of suitable materials include, but are not limited to, MoDTC dimers, MoDTC trimers, MoDTP, etc. In addition, ionic liquids can be used as sulfur-containing metal organic compounds or thiometalates. For example, the ionic liquid can have Formula I:

[0130] [R 1 R 2 R 3 R 4 X] 2 [B x' (A x S y O z ) a' ] I

[0131] in:

[0132] A is selected from one or more of Mo and W;

[0133] When B is present, it is Co and / or Ni;

[0134] x is 1 to 3;

[0135] x' is 0 or 1;

[0136] y is 1 to 13;

[0137] z is 0 to 3;

[0138] a' is 1 or 2;

[0139] R 1 It is C 1 To C 3 alkyl;

[0140] R 2 To R 4 Each independently selected from C 5 To C 20 Alkyl; and

[0141] X is N or P.

[0142] This article may mention [(A x B 1-x ) x' S y O z Examples of ] include, but are not limited to, the following:

[0143] ·Monometallic compounds: [MoS 4 ] 2- 、[MoS9 2- ,[MoOS 3 2- ,[MoOS 3 2- ,[MoO 2 S 2 2- ,[MoO 3 S] 2- ,[WS 4 2- ,[WOS 3 2- ,[WOS 3 2- ,[WO 2 S 2 2- ,[WO 3 S] 2- ;

[0144] ·Polymetallic compound: [Mo 2 S 6 2- ,[Mo 2 S 7 2- ,[Mo 2 S 8 2- ,[Mo 2 S 9 2- ,[Mo 2 S 10 2- ,[Mo 2 S 11 2- ,[Mo 2 S 12 2- ,[Mo 2 OS 7 2- ,[Mo 2 O 2 S 6 2- ,[Mo 2 O 2 S 8 2- ,[Mo 3 S 9 2- ,[Mo 3 S 13 2- ,[W 2 O 2 S 8 2- ​​​​​​​​​​​​​​​​​​​​​;sum

[0145] ·Ni metal compound: [Ni(MoS 4 ) 2 ] 2- , [Ni(MoOS 3 ) 2 ] 2- [Ni(MoO 2 S 2 ) 2 ] 2- [Ni(MoO 3 S) 2 ] 2- , [Ni(WS 4 ) 2 ] 2- , [Ni(WOS 3 ) 2 ] 2- , [Ni(WO 2 S 2 ) 2 ] 2- , [Ni(WO 3 S) 2 ] 2- , [Co(MoS 4 ) 2 ] 2- , [Co(MoOS 3 ) 2 ] 2- , [Co(MoO 2 S 2 ) 2 ] 2- , [Co(MoO 3 S) 2 ] 2- , [Co(WS 4 ) 2 ] 2- , [Co(WOS 3 ) 2 ] 2- , [Co(WO 2 S 2 ) 2 ] 2- , [Co(WO 3 S) 2 ] 2- .

[0146] In the above method, the calcination temperature can be obtained in any suitable manner. This may include placing the sulfur-containing metal organic compound or thiometallate in an environment that has reached the desired temperature, or placing the sulfur-containing metal organic compound or thiometallate in an environment at or near ambient temperature, and gradually raising the temperature to the desired temperature over a period of time. For example, the temperature can be raised at a rate of 3°C to 4°C per minute, such as about 3.5°C per minute, until the target temperature is reached.

[0147] As mentioned above, the temperature of the calcining step may be between 300°C and 400°C. Any temperature within this range may be used. For example, in certain embodiments that may be mentioned herein, the temperature may be about 350°C.

[0148] The time period in step (b) of the above method (i.e. the time period after the desired calcination temperature has been reached) can be any suitable time period that allows the desired catalytic material to be formed. For example, the time period can be 2 hours to 3 hours, such as about 2.5 hours.

[0149] Any suitable inert gas may be used in the calcining step. For example, argon may be used. However, in order to minimize costs, nitrogen may be preferably used.

[0150] As described above, the catalyst disclosed herein can be disposed on a solid support. This can be achieved by uniformly mixing the sulfur-containing metal organic compound or thiometallate with the solid support before step (b) of the above method using the above method. Any suitable solid support can be used. For example, the solid support can be silicon dioxide or a ceramic (e.g., Y-type zeolite).

[0151] The catalyst disclosed herein has been demonstrated to be useful for producing deoxygenated materials at low pressures. Therefore, in another aspect of the present invention, there is provided a method for producing deoxygenated organic materials, the method comprising:

[0152] (a) providing an oxygen-containing raw material and a catalytic material suitable for converting the oxygen-containing raw material into a deoxygenated organic material; and

[0153] (b) contacting the oxygen-containing raw material with the catalytic material in a reaction vessel at a temperature of 275°C to 400°C, such as 300°C to 380°C, at a gas pressure of less than or equal to 2,000 kPa (20 bar) for a period of time to provide the deoxygenated organic material, wherein:

[0154] The oxygen-containing raw material is selected from one or more of the group consisting of triglycerides, fatty acids and fatty acid esters;

[0155] The gas pressure is provided by hydrogen alone, or by hydrogen and an inert gas, wherein the hydrogen is provided by an external hydrogen source and / or is provided internally by hydrogen released from a hydrogen donor; and

[0156] The catalytic material suitable for converting the oxygen-containing raw material into the deoxygenated organic material is selected from one or more of the group consisting of: the catalysts described above and commercially available CoMo catalysts.

[0157] While it is demonstrated herein that CoMo catalysts similar to commercially available materials work in the above process, it is noteworthy that the catalysts described herein are significantly better in the deoxygenation reaction under the conditions specified above.

[0158] In the deoxidation method of organic material, any suitable gas pressure below 2,000 kPa (20 bar) can be used. For example, the pressure can be about 1,000 kPa. As described above, the gas pressure can be provided by hydrogen alone, or by a combination of hydrogen and an inert gas. Although any inert gas can be used, it may be more economical to use nitrogen. In such an embodiment, the main gas pressure can come from nitrogen, and the hydrogen is generated in situ by a hydrogen donor. Therefore, in an embodiment of the present invention using hydrogen and an inert gas, the gas pressure can be provided by hydrogen and nitrogen, and the hydrogen can be provided internally by hydrogen released by a hydrogen donor.

[0159] Any suitable hydrogen donor may be used in the system. It is understood that the hydrogen donor herein should be a material that can release hydrogen and provide a material that can form part of the final product (i.e., the resulting material does not need to be separated from the deoxygenated organic material). In the embodiments of the invention that may be discussed herein, the hydrogen donor may be limonene.

[0160] In embodiments of the invention where a hydrogen donor is present, any suitable weight ratio of oxygen-containing raw material to hydrogen donor may be used. For example, the weight ratio of oxygen-containing raw material to hydrogen donor is from 1:5 to 1:50, such as about 1:9.

[0161] Any suitable weight ratio of catalytic material to raw material may be used in the method. For example, the weight ratio of catalytic material to oxygen-containing raw material may be from 1:15 to 1:50, such as about 1:19.

[0162] As described above, the oxygenated raw material can be formed from one or more triglycerides, fatty acids, and fatty acid esters. Examples of such materials include, but are not limited to, palm oil (e.g., refined palm oil), algae oil (e.g., crude algae oil), canola oil / rapeseed oil, soybean oil, corn oil, sunflower oil, animal fat, olive oil (e.g., virgin or used olive oil), peanut oil, castor oil, animal fat, and combinations thereof.

[0163] Example

[0164] Material

[0165] Zeolite Y powder (Product No. HSZ-320HOA) was obtained from Tosoh. Ammonium tetrathiomolybdate, ethanol, ethyl acetate, magnesium sulfate, ammonium heptamolybdate, cobalt nitrate, γ-alumina, ethylenediaminetetraacetic acid, dichloromethane, and platinum (IV) sulfide were purchased from Sigma-Aldrich and used without any further purification. Methyltrioctylphosphonium methyl carbonate (30% solution in methanol) and methyltrioctylmethylammonium carbonate (50% solution in methanol) were obtained from Proionic.

[0166] Analytical techniques

[0167] SEM

[0168] The surface morphology of the catalyst samples was analyzed using a field emission scanning electron microscope (FESEM) instrument Hitachi SU8020 at 5.0 kV, combined with an energy dispersive X-ray (EDX) spectrometer operating at 20.0 kV.

[0169] XRD

[0170] XRD analysis was performed using Cu Ka radiation (λ=0.154 nm) at 40 kV and 40 mA on a Shimadzu X-ray diffractometer 7000. The obtained XRD patterns were analyzed using Qualx software and the Crystallography Open Database (POW-COD) database.

[0171] GC-MS

[0172] GC-MS (Perkin Elmer Clarus 500) was equipped with a Restek Rxi-5Sil MS (0.25MM id x60m) column. Helium was used as carrier gas and dichloromethane was used as solvent. The inlet GC temperature was set to 380°C, the oven temperature was increased to 330°C at a rate of 7°C / min and maintained at 330°C for 15 minutes. Compounds were identified by comparison with the spectral data available in the NIST library.

[0173] Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES)

[0174] The contents of active metals Cu-Ni on the supports were characterized by ICP-OES using a Perkin Elmer Optima DV 5300 spectrometer.

[0175] General procedure for deoxygenation reactions

[0176] The deoxygenation reaction was carried out in a 200 mL Buchi stainless steel batch autoclave reactor. The reactor was designed to operate at up to 500 °C and 350 bar and was heated by an electric furnace. The reactor was also equipped with a single blade impeller for stirring, a K-type thermocouple, an internal cooling coil, and an analog pressure gauge.

[0177] Example 1 Bis(trioctylmethylphosphonium)tetrathiomolybdate ([TOMP] 2 MoS 4 ) (G.Alonso et al., Catal. Today 1998, 43, 117-122, US4370245)

[0178] Ammonium tetrathiomolybdate (ATTM, 1.35 g, 5.1 mmol) was dissolved in water (20 mL) to give a clear red solution. To this solution was added a solution of methyltrioctylmethylphosphonium carbonate (30% methanol solution, 15.8 g, 10.3 mmol) diluted in ethanol (15 mL) under vigorous stirring. The separated red viscous ionic liquid was extracted with ethyl acetate and purified by MgSO 4 The volatiles were removed under reduced pressure to obtain a nearly quantitative yield of a dark red viscous ionic liquid (IL) ([TOMP] 2 MoS 4 ).

[0179] FTIR (NaCl sheet): 472cm -1 (Mo-S); UVλ max (nm,MeCN):474,322,245,200.

[0180] Example 2 Bis(trioctylmethylammonium)tetrathiomolybdate ([TOMA] 2 MoS 4 ) (G.Alonso et al., Catal. Today 1998, 43, 117-122, US4370245)

[0181] Bis(trioctylmethylammonium)tetrathiomolybdate was prepared from ATTM (0.68 g, 2.6 mmol) and trioctylmethylammonium chloride (2.1 g, 5.2 mmol) diluted in ethanol (15 mL) according to the protocol in Example 1, except that 15 mL of water was used. The separated red viscous ionic liquid was extracted with ethyl acetate and purified by MgSO 4 The volatiles were removed under reduced pressure to obtain bis(trioctylmethylammonium)tetrathiomolybdate in nearly quantitative yield as a dark red viscous ionic liquid.

[0182] FTIR (NaCl sheet): 474cm -1 (Mo-S); UVλ max (nm,MeCN):474,322,245,200.

[0183] Example 3 Bis(dioctadecyldimethylammonium)tetrathiomolybdate ([DODMA] 2 MoS 4 ) (G.Alonso et al., Catal. Today 1998, 43, 117-122, US4370245)

[0184] [DODMA] was prepared according to the protocol in Example 1 from a solution of ATTM (0.98 g, 3.8 mmol) and dioctadecyldimethylammonium chloride (4.2 g, 7.5 mmol) dissolved in warm ethanol (15 mL). 2 MoS 4 The brick-red solid was isolated by filtration, washed with copious amounts of water and ethanol, and dried in vacuo to afford [DODMA] in near quantitative yield. 2 MoS 4 .

[0185] FTIR(KBr Pill):469cm -1 (Mo-S); UVλ max (nm,MeCN):474,322,245,200.

[0186] Example 4 Synthesis of unsupported P Mo-oxide (P MoOx) catalyst

[0187] By calcining the ionic liquid ([TOMP]) in a furnace under air flow 2 MoS 4 , prepared in Example 1) to prepare a PMoOx catalyst. The sample was heated to 350°C at a rate of 3.5°C / min and maintained at this temperature for 2 hours.

[0188] Example 5 Synthesis of unsupported P Mo-sulfide (P MoSx) catalyst

[0189] The ionic liquid (TOMP) was calcined in an autoclave with nitrogen flow. 2 MoS 4 , prepared in Example 1) to prepare P MoSx catalyst. The sample was heated to 350°C at a rate of 4°C / min and kept at this temperature for 2.5 hours.

[0190] Example 6 Synthesis of Silica-Supported P MoSx Catalyst

[0191] [TOMP] 2 MoS 4 The ionic liquid (6.0 g, prepared in Example 1) was mixed with silica powder (4.0 g) in an autoclave. After vigorous mixing for 10 minutes, the mixture was heated to 350° C. at a rate of 3.5° C. / min under an inert nitrogen flow. Then, the mixture was kept heated at 350° C. for 2 hours.

[0192] Example 7 Synthesis of Y-type zeolite supported P MoSx catalyst

[0193] A Y-type zeolite-supported P MoSx catalyst was prepared according to the protocol in Example 6, except that Y-type zeolite powder (4.0 g) was used instead of silica powder.

[0194] Example 8 Synthesis of Unsupported N Mo-Sulfide (MoSx-N) Catalyst

[0195] The ionic liquid ([TOMA]) was calcined in an autoclave with nitrogen flow. 2 MoS 4 , prepared in Example 2) to prepare MoSx-N catalyst. The sample was heated to 350°C at a rate of 3.5°C / min and maintained at this temperature for 2 hours.

[0196] Example 9 Synthesis of Silica-Supported MoSx-N Catalyst

[0197] Will [TOMA] 2 MoS 4 The ionic liquid (1.0 g, prepared in Example 2) was mixed with silica powder (1.0 g) in an autoclave. After vigorous mixing for 10 minutes, the mixture was heated to 350° C. at a rate of 5.3° C. / min under an inert nitrogen flow. Then, the mixture was kept heated at 350° C. for 2 hours.

[0198] Example 10 Synthesis of Y-type zeolite-supported MoSx-N catalyst

[0199] The MoSx-N catalyst was prepared according to the protocol in Example 9, except that Y-type zeolite powder (1.0 g) was used instead of silica powder.

[0200] Example 11 Synthesis of Zirconia-Supported Mo-Sulfide Catalyst

[0201] ATTM (3.1 g) was mixed with zirconium oxide powder (4.5 g) and acetone (150 mL). After vigorous mixing for 10 minutes, the mixture was heated to 350° C. at a rate of 5.3° C. / min under an inert nitrogen flow. Then, the mixture was kept heated at 350° C. for 2 hours.

[0202] Example 12 Synthesis of ZSM5 Zeolite Supported Mo-Sulfide Catalyst

[0203] A ZSM5 zeolite-supported Mo-sulfide catalyst was prepared according to the protocol in Example 11, except that ZSM5 powder (4.5 g) was used instead of zirconia powder.

[0204] Example 13 Synthesis of ZSM5 Zeolite Supported NiMo-Sulfide (NiMoSx) Catalyst

[0205] ATTM (1.0 g) was mixed with ZSM5 powder (4.5 g), nickel nitrate hexahydrate (1.0 g) and acetone (150 mL). After vigorous mixing for 10 minutes, the mixture was heated to 350° C. at a rate of 5.3° C. / min under an inert nitrogen flow. Then, the mixture was kept heated at 350° C. for 2 hours.

[0206] Example 14 Synthesis of bulk CoMo catalyst (CoMo5) at pH 5

[0207] The bulk CoMo catalyst was synthesized using the known deposition precipitation (DP) method. Ammonium heptamolybdate (NH 4 ) 6 Mo 7 O 24 (2.648 g, 0.015 mol Mo) and cobalt nitrate Co(NO 3 ) 2 6H 2 O (4.366 g, 0.015 mol of Co) was dissolved in deionized (DI) water (200 mL). While heating, 100 mL of alkaline aqueous solution was added dropwise and a significant color change was observed. For catalyst precipitation under pH 5 conditions, urea solution (30% concentration) was used as the alkaline solution. After adding the alkaline solution, the temperature was balanced at 90°C for 6 hours and then cooled to ambient temperature. The suspension was vacuum filtered, then washed three times with deionized water, and the solid catalyst sample was dried at 80°C overnight and then calcined at 460°C for 4 hours in a tubular furnace with flowing air (flow rate: 2 L / min).

[0208] The general process of catalyst sulfidation is to use dimethyl disulfide (DMDS) and hydrogen (H 2 ) produces H 2 S, to sulfide MoO to MoS 2 In a sealed autoclave reactor, the catalyst and DMDS were mixed at a rate of 1.39 mL DMDS / g catalyst to 50 bar H 2The reactor is slowly heated to 150°C, and an exothermic effect can be seen, where the internal temperature of the reactor increases by 10-20°C above the temperature set point (SP) of the reactor. For reference, the decomposition temperature of DMDS is between 175-205°C. When the internal temperature of the reactor tends to stabilize and approaches the temperature SP, the SP is slowly increased again (in increments of 15-20°C) until the temperature SP reaches 230°C. After reaching the temperature SP of 230°C, the sulfidation reaction is maintained for one hour, which is considered to be the first stage of catalyst sulfidation. Special attention should be paid not to exceed 245°C to avoid coking problems and catalyst deactivation. Similar steps are repeated while the temperature SP is increased to 345°C and maintained for one hour in the second stage of sulfidation.

[0209] Example 15 Synthesis of bulk CoMo catalyst (CoMo9) at pH 9

[0210] The bulk CoMo catalyst was prepared according to the protocol in Example 14, except that 10% NH 4 The catalyst was precipitated by OH solution at pH 9.

[0211] Example 16 Alumina Al 2 O 3 Synthesis of supported CoMo catalyst

[0212] Using IWI method to prepare γ-alumina Al 2 O 3 The supported CoMo catalyst was synthesized as the carrier. The effect of chelating agent on the catalytic deoxygenation performance was studied, wherein the chelating agent used was ethylenediaminetetraacetic acid (EDTA).

[0213] Ammonium heptamolybdate (NH 4 ) 6 Mo 7 O 24 (2.1 g) and cobalt nitrate Co(NO 3 ) 2 6H 2 O(1.6g) and γ-Al 2 O 3 (4.5 g) and EDTA (0.5 g) were dissolved in deionized water (200 mL). The solution was stirred at 30° C. for 6 hours. After impregnation, the catalyst was dried at 80° C. overnight and then calcined at 460° C. for 4 hours in a tube furnace with flowing air (flow rate: 2 L / min).

[0214] Example 17 Alumina Al 2 O 3 Synthesis of supported CoMo catalyst

[0215] The supported CoMo catalyst was prepared according to the protocol in Example 16, except that EDTA was not added as chelating agent. The suspension was filtered, washed, dried and calcined according to the protocol in Example 15.

[0216] Example 18 Synthesis of P MoSx Catalyst from MoDTP

[0217] Commercially available molybdenum dithiophosphate (MoDTP) was calcined using the procedure described in Example 5 to produce a catalyst powder.

[0218] Example 19 Hydrodeoxygenation Reaction—Low H 2 Pressure (LP)

[0219] The deoxygenation of palmitic acid was investigated as a general test reaction to examine the suitability of the catalyst. The deoxygenation reaction was carried out in a 200 mL Buchi steel batch autoclave reactor. The reactor was designed to operate at up to 500 °C and 350 bar pressure and was equipped with an electric furnace heating. The reactor was also equipped with a single blade impeller for stirring, a K-type thermocouple, an internal cooling coil and an analog pressure gauge.

[0220] About 1 g of the catalyst was placed in a 200 mL autoclave reactor containing 19 g of palmitic acid. The reactor was then immediately sealed and heated with H 2 The reactor was purged (5 times) to remove air. 2 The reactor was pressurized to 10 bar and the temperature was raised from room temperature to the target reaction temperature at a heating rate of 4°C / min. When the reaction reached the target temperature, a timer was started and the stirring rate was set to 1000 rpm. The temperature trend was recorded using Buchi's data logging software BLS3. After the deoxygenation reaction ran for the target duration, the furnace was turned off and cooling water was supplied to the reactor via an internal cooling coil controlled by the BLS3 software.

[0221] Example 20 Hydrodeoxygenation Reaction—H 2 Donor (HD)

[0222] Deoxygenation of palmitic acid was carried out according to the protocol in Example 19, except that a trial run was performed using limonene as the hydrogen donor.

[0223] 0.26 g of catalyst was used in palmitic acid (5 g) and limonene (50 mL) to give a catalyst to palmitic acid feedstock weight ratio of 1:19. Unless otherwise stated, the typical concentration of palmitic acid in limonene was 10.7 wt % relative to limonene in all reactions. The reactor was then immediately sealed and heated with N 2 The reactor was purged (5 times) to remove oxygen. 2The reactor was pressurized to 5 bar and the reaction was carried out according to the protocol in Example 19.

[0224] Example 21 Hydrodeoxygenation Reaction—High H 2 Pressure (HP)

[0225] Deoxygenation of palmitic acid was carried out according to the protocol of Example 19, except that the 2 Test run under pressure.

[0226] Example 22 Characterization of MoSx Catalyst

[0227] The catalyst used in the present invention is prepared by calcining a tetrathiomolybdate ionic liquid having a tetraalkylphosphonium cation under an inert atmosphere (see Example 5).

[0228] The product obtained from this process is a black brittle solid with a porous sponge-like macroscopic appearance ( Figure 1 The final yield was about 20%, which was due to the loss of volatile organic decomposition products of the cation. The morphology of the catalyst was studied by SEM, and the micrographs revealed a microstructure consisting of randomly arranged layers that spread out radially to form approximately spherical clusters ( Figure 2 ). The XRD pattern of the unsupported MoSx catalyst shows the typical morphology of weakly crystalline materials, indicating the formation of disordered MoS 2 Particles ( Figure 3 ).

[0229] Example 23 Catalytic Performance of MoSx Catalyst

[0230] By following the protocol in one of Examples 19 to 21, the catalytic performance of the MoSx catalyst (prepared in Examples 4-18) was evaluated relative to CoMo, the most common catalyst used industrially for the HDO process.

[0231] Measurement of Brunnauer-Emmet-Teller (BET) value

[0232] The catalyst powder samples were characterized by nitrogen physical adsorption (Micromeritics ASAP 2020) to obtain adsorption and desorption plots. The catalyst samples were degassed at 250 °C for 12 h. The surface area was quantified by the BET technique, while the pore diameter and volume were calculated by P / P o It is determined by the volume of nitrogen adsorbed when the value is 0.985.

[0233] Results and discussion

[0234] The model reaction was the HDO of palmitic acid using D-limonene as the low-pressure hydrogen donor (Table 1).

[0235] Table 1 Catalyst compositions and catalysts at 370 °C (unless otherwise stated) using palmitic acid and H 2 Performance during HDO model reactions at 10 bar (low pressure, LP), 60 bar (high pressure, HP) or D-limonene (hydrogen donor, HD)

[0236]

[0237]

[0238]

[0239] *ICP-OES test performed before catalyst sulfidation.

[0240] GC-MS analysis of the reaction products obtained over the MoSx catalyst showed almost complete depletion of the palmitic acid feedstock, formation of C15 and C16 products originating from HDO and decarbonylation / decarboxylation pathways, and aromatic peaks associated with the dehydrogenation / rearrangement of D-limonene.

[0241] The catalyst outperformed the CoMo9 catalyst, showing a palmitic acid conversion of 95%, while CoMo9 had a palmitic acid conversion of 88.9%. As a control test, the MoOx catalyst had a much lower conversion of 45.5%, indicating the inherent catalytic activity of the metal sulfide. When high-pressure hydrogen (60 bar) was used, the conversion of CoMo9 increased to over 99%, highlighting its effectiveness for conventional industrial processes. Under the same high-pressure conditions, the MoSx catalyst achieved similar conversions and selectivities, which confirms its wider range of applications. The best performance of MoSx was recorded under low-pressure hydrogen (10 bar), resulting in an extraordinary conversion of 99% and a selectivity of over 95%. However, when the reaction temperature was reduced to 350°C and 330°C, a decrease in catalytic activity was observed, resulting in conversions of 93% and 65%, respectively.

[0242] In Examples 6 and 7, silica-supported and Y-zeolite-supported MoSx catalysts were also prepared by the same method described in Example 5, except that the ionic liquid was uniformly mixed with the support material before calcination. Both supported catalysts showed suppressed catalytic activity, with the conversion of silica-supported MoSx and Y-zeolite-supported MoSx reduced to 22% and 45.5%, respectively. Obviously, the use of bulk MoSx (in which the catalytically active material is not diluted by inert materials) increases the number of active sites available for catalysis, thereby improving the conversion. In addition, it cannot be ruled out that the interaction with the support may change the micro- and nanostructure of the MoSx material, resulting in reduced catalytic activity.

[0243] Example 24 Effect of Initial Ionic Liquid Cations on Catalytic Performance

[0244] The effect of the starting ionic liquid cation on the catalytic performance was studied according to the protocol in Example 20. In Example 8, an analog of MoSx (MoSx-N) was prepared.

[0245] Results and discussion

[0246] No obvious differences were observed in the final materials, and the MoSx-N catalyst showed excellent activity for HDO of palmitic acid with D-limonene as the hydrogen donor. These results suggest that the performance of the catalysts depends mainly on the MoS 2 The presence of ingredients and the size of the cation, rather than the type of "onium" salt (i.e. ammonium vs. phosphonium).

[0247] Example 25 Catalytic Performance of MoSx Catalyst for HDO of Oil

[0248] The performance of the MoSx catalyst (prepared in Example 5) in HDO was tested in addition to the model reaction of free fatty acids. Therefore, three different oils (i.e., refined palm oil, crude algae oil, and sunflower oil) were used as feedstocks for HDO according to the protocol in Examples 20 and 21.

[0249] Results and discussion

[0250] The conversion rates for all examples were over 99% (Table 2). This confirms the applicability of the proposed method and achieves excellent results in real example systems.

[0251] Table 2 HDO reaction results of P-MoSx catalyst using different raw materials.

[0252] raw material <![CDATA[H 2 Source]]> HDO conditions temperature Conversion rate (%) Refined palm oil <![CDATA[60 bar H 2 > HP 370℃ >99 Crude algae oil <![CDATA[60 bar H 2 > HP 370℃ >99 Sunflower Oil D-Limonene HD 370℃ >99

Claims

1. A weakly crystalline metal sulfide catalyst, wherein the catalyst comprises: Mo and / or W in a total amount of 25 to 35 wt.%; A total amount of 0 wt% to 25 wt% Ni and / or Co; S in an amount of 20 to 28 wt %; N or P in an amount of 0 to 5 wt%; and 10 to 54 wt. % C, wherein: When Mo and W are present, they are in the form of MoS2 and / or MoS3, WS2 and / or WS3 or Mo a W 1-a S y In the form of particles, wherein a is from 0.99 to 0.01, and y is 2 and / or 3; and The crystallinity of the catalyst measured by powder X-ray crystal diffraction is less than 80%.

2. The catalyst according to claim 1, wherein the BET surface area of ​​the catalyst is 75 m 2 / g to 100m 2 / g.

3. The catalyst according to claim 1 or 2, wherein the catalyst comprises: Mo and / or W in a total amount of 25 to 35 wt.%; A total amount of 0 wt% to 25 wt% Ni and / or Co; S in an amount of 20 to 28 wt %; N or P in an amount of 0 to 5 wt%; and 32 to 54 wt% C; or Mo and / or W in a total amount of 27 to 30 wt.%; A total amount of 0 to 20 wt% Ni and / or Co; S in an amount of 22 to 24 wt %; N or P in an amount of 3 to 4 wt%; and The content of C is 42% to 48% by weight.

4. The catalyst according to any one of the preceding claims, wherein the catalyst comprises: Mo in a total amount of 25 wt% to 35 wt%; S in an amount of 20 to 28 wt %; N or P in an amount of 1 to 5 wt%; and The content of C is 32% to 54% by weight.

5. The catalyst according to claim 4, wherein the catalyst comprises: Mo in an amount of 27 to 30 wt %, for example about 28.9 wt %; S in an amount of 22 to 24 wt %, for example, about 23.2 wt %; N or P in an amount of 3 to 4 wt%, for example, about 3.5 wt%; and The content of C is 42% to 48% by weight, for example, about 44.4% by weight.

6. The catalyst according to claim 4 or 5, wherein the X-ray powder diffraction pattern shows broad peaks with 2θ values ​​of about 33° and about 59°.

7. The catalyst according to any one of claims 4 to 6, wherein the BET surface area is about 83.6 m 2 / g.

8. A catalyst according to any one of the preceding claims, wherein: (a) the catalyst has a crystallinity of less than 70%, such as less than 60%, such as less than 50%; and / or (b) The catalyst is attached to a solid support, optionally wherein the solid support is silica or a ceramic (eg Y-zeolite).

9. A method of forming a catalyst according to any one of claims 1 to 8, the method comprising the steps of: (a) providing a sulfur-containing metal organic compound or a thiometallate; and (b) calcining the sulfur-containing metal organic compound or thiometalate under an inert gas flow at a temperature of 300° C. to 400° C. for a period of time to provide the catalyst.

10. The method according to claim 9, wherein the temperature is increased at a rate of 3 to 4°C per minute, such as about 3.5°C per minute, until the target temperature is reached.

11. The method according to claim 9 or 10, wherein: (i) the temperature is about 350°C; and / or (ii) prior to step (b) of claim 9, homogeneously mixing the sulfur-containing metal organic compound or thiometallate with a solid support, optionally wherein the solid support is silica or a ceramic (eg, Y-zeolite).

12. A method according to any one of claims 9 to 11, wherein the time period after reaching a temperature of 300 to 400°C is 2 to 3 hours, such as about 2.5 hours.

13. The method according to any one of claims 9 to 12, wherein the inert gas is nitrogen.

14. A method for producing a deoxygenated organic material, the method comprising: (a) providing an oxygen-containing raw material and a catalytic material suitable for converting the oxygen-containing raw material into a deoxygenated organic material; and (b) contacting the oxygen-containing raw material with the catalytic material in a reaction vessel at a temperature of 275°C to 400°C, such as 300°C to 380°C, at a gas pressure of less than or equal to 2,000 kPa (20 bar) for a period of time to provide the deoxygenated organic material, wherein: The oxygen-containing raw material is selected from one or more of the group consisting of triglycerides, fatty acids and fatty acid esters; The gas pressure is provided by hydrogen alone, or by hydrogen and an inert gas, wherein the hydrogen is provided by an external hydrogen source and / or is provided internally by hydrogen released from a hydrogen donor; and The catalytic material suitable for converting the oxygen-containing raw material into a deoxygenated organic material is selected from one or more of the group consisting of a catalyst according to any one of claims 1 to 8 and a commercially available CoMo catalyst (e.g., a catalyst according to any one of claims 1 to 8).

15. The method of claim 14, wherein the pressure is about 1,000 kPa.

16. The method according to claim 14 or 15, wherein the gas pressure is provided by hydrogen and nitrogen, and the hydrogen is provided internally by hydrogen released by the hydrogen donor.

17. The method according to any one of claims 14 to 16, wherein the hydrogen donor is limonene.

18. A method according to any one of claims 14 to 17, wherein the weight ratio of the catalytic material to the oxygen-containing raw material is from 1:15 to 1:50, such as about 1:

19.

19. The method according to any one of claims 14 to 18, wherein: When a hydrogen donor is present, the weight ratio of the oxygen-containing raw material to the hydrogen donor is from 1:5 to 1:50, such as about 1:

9.

20. The method according to any one of claims 14 to 29, wherein the raw material is selected from one or more of the following: palm oil (e.g. refined palm oil), algal oil (e.g. crude algal oil), canola oil / rapeseed oil, soybean oil, corn oil, sunflower oil, tallow oil, olive oil (e.g. virgin or used olive oil), peanut oil, castor oil and animal fat.

21. The method according to any one of claims 14 to 29, wherein the sulfur-containing metal organic compound or thiometalate is an ionic liquid having formula I: [R1R2R3R4X]2[B x' (A x S y O z ) a' ]I in: A is selected from one or more of Mo and W; When B is present, it is Co and / or Ni; x is 1 to 3; x' is 0 or 1; y is 1 to 13; z is 0 to 3; a' is 1 or 2; R1 is C1 to C3 alkyl; R2 to R4 are each independently selected from C5 to C 20 Alkyl; and X is N or P.